Mathematical Problem Solving Capabilities: Self-confidence, Self-efficacy, Emotional Intelligence, and Concept Understanding Ability - Syaipul Amri; Wahyu Widada; Agus Susanta; Zamzaili Zamzaili (University of Bengkulu, 2020)
Mathematics is a compulsory subject in all of Indonesian high school. Problem solving ability is a competency that must be possessed in learning mathematics. The purpose of this study was to examine the variables that affect the ability to solve mathematical problems. These variables are self confidence, self efficacy, emotional intelligence, and the ability to understand concepts. This is a survey research, with a sample of 100 people. The sample was selected by simple random technique from all high school students in Bengkulu City. There are five instruments of this research, namely a test of mathematical problem-solving ability, a concept comprehension ability test, and three questionnaires for self confidence, self efficacy, as well as an emotional intelligence questionnaire. Research data were analyzed through path analysis using SPSS and the Lisrel Application Program. The results of this study were the variables of self confidence, self efficacy, emotional intelligence, and the ability to understand concepts have a direct positive effect on the ability to solve mathematical problems. From this research, we conclude that the ability to solve mathematical problems through self-confidence, self-efficacy, emotional intelligence, and the ability to understand concepts students were in a good category.